Student Politics in Africa Representation and Activism - Luescher, Thierry M. (African Minds, 2016)
The second volume of the African Higher Education Dynamics Series brings together the research of an international network of higher education scholars with interest in higher education and student politics in Africa. Most authors are early career academics who teach and conduct research in universities across the continent, and who came together for a research project and related workshops and a symposium on student representation in African higher education governance. The book includes theoretical chapters on student organising, student activism and representation; chapters on historical and current developments in student politics in Anglophone and Francophone Africa; and in-depth case studies on student representation and activism in a cross-section of universities and countries. The book provides a unique resource for academics, university leaders and student affairs professionals as well as student leaders and policy-makers in Africa and elsewhere.